Saberes e práticas sobre reprovações no processo de ensino-aprendizagem do curso de Engenharia Elétrica da UFU: um estudo a partir da Teoria das Representações Sociais - Araújo, Leia Souza Alves de (2003)
This research was developed in the Master in Education of the Federal University of Uberlândia, in the period 2001/2002, with the objective of analyzing the knowledge and practices failures in the teaching-learning process of the Electrical Engineering course at UFU, with a focus on understanding the forms, meaning and function of evaluative practices in failures in the context of the subjects surveyed (students, teachers); seeking to apprehend the relationship between social representations about this phenomenon and its repercussions on the interactions between teacher and student, in the teaching-learning process and in the perpetuation or transformation of educational practices carried out in the Electrical Engineering course at UFU. It is a research with an emphasis on qualitative aspects, but which contains many quantitative data that served as a subsidy for the choice of the interviewed subjects, of the researched aspects, and to present the failure rates in the period from 1997 to 2001 in a more systematic way , referring to the disciplines common to the two emphases existing in the course: Electronics and Electrotechnics. The interviewed subjects were eight students who had already taken the five subjects that presented the highest failure rates in the defined period, which are: Electromagnetism, Material Mechanics, Electrical Circuits 1, Differential and Integral Calculus 3 and Electrical Materials 1; and three teachers from those same disciplines. In the interviews, in the However, the focus was not only on the five disciplines mentioned, because what was sought to understand and analyze in a more approximate way was the factors that caused the failures, without specifying any discipline. It was based on the assumption that there were ideas, attitudes, behaviors produced in the space socially shared by the group and that these circulated and strongly influenced the perpetuation of failures, which is characteristic of a social representation. To better understand the phenomenon of failures, a historic rescue of the Faculty of Electrical Engineering at UFU was carried out, engineering education and training was discussed in general and a study on learning assessment. The analyzes developed here show that the facing the problem of failures in the Electrical Engineering course at UFU, as well as engineering courses at other institutions implies improving the teaching-learning process learning and training of engineering teachers. It also implies the need for a dynamic and global understanding of the context and everyday life of the course, in order to break with those conservative and authoritarian views, attitudes and practices that favor the perpetuation of phenomena such as failures, and that generate passivity and conformism. between teachers and students.